A bibliometric review of research on simulations and serious games used in educating for sustainability, 1997–2019. (20th May 2020) - Hallinger, Philip; Wang, Ray; Chatpinyakoop, Chatchai; Nguyen, Vien-Thong; Nguyen, Uyen-Phuong
Abstract: Scholars have noted a recent proliferation of simulations and serious games developed for use in educating for sustainability. However, to date, reviews of research have focused on the use of simulations and games in specific subject domains of sustainability such as energy, climate change, and natural resource management. This bibliometric review addressed this gap by documenting and analyzing the full span of research on simulations and serious games used in educating for sustainability. The review aimed to document the growth trajectory, types of documents, topical foci, modes of delivery, and geographical distribution of this literature. Then the authors analyzed research designs and methods employed in this research. The authors applied descriptive statistics and content analysis to 376 relevant Scopus/Google Scholar-indexed documents describing the use of simulations and serious games in educating for sustainability. Key results highlighted the recent vintage of this literature as well as a predominance of studies from a relatively small set of Western societies. The simulations and serious games described in these documents encompass foci on environmental, economic and social sustainability. Technology-enhanced simulations and games are most prevalent, and higher education settings the most common venues of use in this literature. The knowledge base is overly weighted towards 'commentaries' (55%) and lacks a critical mass of empirical studies (33%). Moreover, the empirical knowledge base is dominated by studies that rely on non-experimental research designs and descriptive methods. The authors highlight a variety of stronger research designs and methods that can be used as models for future research. This aligns with a key recommendation for scholars in this domain to undertake programmatic research aimed at substantiating the effects of simulations and serious games on learner attitudes, knowledge and behavior. Highlights: Reviewed 376 documents describing use of serious games used in educating for sustainability. Concluded this is a literature of recent vintage that has emerged largely since 2010. Highlighted the wide range of topics and coverage of the full triple bottom-line. Found an insufficient mass of empirical studies suggesting a prescriptive literature. Highlighted models of stronger research designs and methods for use in future studies.